Predictors of Hip Pain and Function in Femoroacetabular Impingement: A Prospective Cohort Analysis. Issue 7 (21st July 2017) - Westermann, Robert W.; Lynch, Thomas Sean; Jones, Morgan H.; Spindler, Kurt P.; Strnad, Greg; Messner, William; Rosneck, James T.
Objectives: Joint pain and function at the time of surgery may influence postoperative rehabilitation, recovery and the final outcome of the patient. Little is known about how patient factors or pathologic findings predict hip pain or function in those presenting with femoroacetabular impingement (FAI). We hypothesized that patient factors including mental health would more strongly correlate with subjective assessments of hip pain and function compared to the extent of the intra- or extra-articular pathology (chondral damage, labral tear, cam or pincer deformities) in patients undergoing surgery for FAI. Methods: A prospective cohort of patients undergoing hip arthroscopy for FAI were enrolled between 2/2015 and 9/2016. Patients d HOOS-Pain, HOOS-Physical Function, VR12-MCS, VR12-PCS and UCLA activity questionnaires at the time of surgery. Surgeons documented intra-articular operative findings for each case by a standardized data collection method utilizing a mobile iPhone application. Multivariable linear regression models were created for continuous scores of HOOS-pain, HOOS-Physical Function and VR12-PCS as dependent variables. Independent variables studied included both patient factors and intra-operative anatomic and pathologic findings [Table 1]. Results: During the study period, 396 patients undergoing arthroscopic surgery for FAI were enrolled. The mean patient age was 34±14 years, mean BMI 26.36±5.01 and 71% were female. The mean baseline scores were 45.94±17.07 for HOOS-Pain, 31.68±10.06 for VR-12 PCS and 40.99±17.75 for HOOS-Physical Function. The mean UCLA activity score was 5.04±2.57. Factors associated with worse HOOS-Pain scores include older age (p=0.01), female sex (p<0.001), smoking (p<0.001), years of education (p<0.001), lower VR-12 Mental Component Scores (p<0.001), lower UCLA activity scores (p<0.001) and presence of a labral tear diagnosed on hip arthroscopy (p=0.046) [Table 1]. Factors associated with worse HOOS-Physical function include female sex (p=0.004), smoking (p=0.01), fewer years of education (p=0.02), lower VR-12 MCS (p=0.002), and lower activity level (p<0.001). Factors associated with worse VR-12 PCS include increased age (p<0.001), female sex (p=0.02), smoking (p<0.001), and lower activity level (p<0.001). Conclusion: Patients with lower mental health scores, lower activity levels and those who smoke have predictably worse subjective hip pain and function when controlling for operative variables. While the presence of a labral tear does predict worse pain, the impact on subjective pain is weaker compared to patient factors such as mental health, smoking or female sex. Future studies evaluating patient outcomes after surgery for FAI should consider correcting for these identified patient factors in order to accurately interpret differences in patient reported outcomes. In order to determine the influence of these factors on the final outcome of the patient, further studies and follow-up are warranted.